2014
DOI: 10.1080/00223891.2014.963591
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Multidimensional Perfectionism Scale of Hewitt in a Dutch-Speaking Sample: Associations With the Big Five Personality Traits

Abstract: This article may not exactly replicate the final published article. It is not the copy of the record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
2
20
0
12
Order By: Relevance
“…Flett and Hewitt (2015) point out in their review of perfectionism measures that Cox et al (2002), when developing their MPS short form, did not take into account a possible wording factor: Items that are negatively worded may load on a different factor from items that are positively worded (see De Cuyper, Claes, Hermans, Pieters, & Smits, 2015). Moreover, research has shown that the use of negatively worded items can be problematic because it is unclear if such items capture the intended construct in the same way as COMPARING TWO SHORT FORMS OF THE HEWITT-FLETT MPS 5 positively worded items (DiStefano & Motl, 2006;Sinclair & Tetrick, 2000).…”
Section: Comparing Two Short Forms Of the Hewitt-flett Mpsmentioning
confidence: 99%
“…Flett and Hewitt (2015) point out in their review of perfectionism measures that Cox et al (2002), when developing their MPS short form, did not take into account a possible wording factor: Items that are negatively worded may load on a different factor from items that are positively worded (see De Cuyper, Claes, Hermans, Pieters, & Smits, 2015). Moreover, research has shown that the use of negatively worded items can be problematic because it is unclear if such items capture the intended construct in the same way as COMPARING TWO SHORT FORMS OF THE HEWITT-FLETT MPS 5 positively worded items (DiStefano & Motl, 2006;Sinclair & Tetrick, 2000).…”
Section: Comparing Two Short Forms Of the Hewitt-flett Mpsmentioning
confidence: 99%
“…Sin embargo, aseguran que la consideración del PAO como un rasgo positivo se debe a la confusión de este constructo con la conciencia, uno de los cinco grandes rasgos de la personalidad (véase John y Srivastava, 1999, para una revisión). En este sentido, son diversas las investigaciones que han analizado la relación entre el PAO y el modelo de los cinco grandes rasgos: Extraversión, Neuroticismo, Conciencia, Apertura a la Experiencia y Cordialidad (Cuttler y Graf, 2007;De Cuyper, Claes, Hermans, Pieters y Smits, 2015;Dunkley y Kyparissis, 2008;Hill, McIntire y Bacharach, 1997;Nathanson, Paulhus y Williams, 2006;Sherry, Hewitt, Flett, LeeBaggley y Hall, 2007;Stoeber, Otto y Dalbert, 2009). Hill et al (1997) encontraron, en una muestra de 214 universitarios estadounidenses con una edad media de 19 años, que el PAO correlacionó positiva y significativamente tan sólo con Conciencia.…”
Section: Antecedentesunclassified
“…Más recientemente, en 959 universitarios belgas entre 15 y 37 años, De-Cuyper et al (2015) observaron que el PAO predijo significativamente y en sentido positivo los rasgos de Conciencia y Apertura a la experiencia, así como en sentido negativo el Neuroticismo y la Extraversión. No obstante, el PAO no alcanzó la significación estadística en su relación con la Cordialidad.…”
Section: Antecedentesunclassified
See 2 more Smart Citations